2018
DOI: 10.1074/jbc.ra118.005796
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional coactivator WBP2 primes triple-negative breast cancer cells for responses to Wnt signaling via the JNK/Jun kinase pathway

Abstract: The transcriptional coactivator WW domain-binding protein 2 (WBP2) is an emerging oncogene and serves as a node between the signaling protein Wnt and other signaling molecules and pathways, including epidermal growth factor receptor, estrogen receptor/progesterone receptor, and the Hippo pathway. The upstream regulation of WBP2 is well-studied, but its downstream activity remains unclear. Here, we elucidated WBP2's role in triple-negative breast cancer (TNBC), in which Wnt signaling is predominantly activated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 81 publications
4
47
1
Order By: Relevance
“…It is conceivable that WBP2 possesses nonnuclear functions that remain to be discovered. This notion is supported by the results arising from the interrogation of the proteomics data against the RNA-seq data which showed that 30% of the WBP2-target proteins were regulated at the mRNA level, whereas the majority were regulated at the posttranscriptional or posttranslational level [33].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 71%
See 3 more Smart Citations
“…It is conceivable that WBP2 possesses nonnuclear functions that remain to be discovered. This notion is supported by the results arising from the interrogation of the proteomics data against the RNA-seq data which showed that 30% of the WBP2-target proteins were regulated at the mRNA level, whereas the majority were regulated at the posttranscriptional or posttranslational level [33].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 71%
“…A glimpse into the global mode of action of WBP2 in Wnt signaling was revealed through the work of our group in which RNA-seq was employed to ascertain the pervasiveness of WBP2 in Wnt signaling [33]. More than 80% of the Wntinduced genes in MDA-MB-231 TNBC cells were demonstrated to be dependent on WBP2.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature reveals the relevant situation downstream of JNK. For example, IL-2/sorafenib can affect tumor survival, growth and mobility through JNK-TAZ pathways (41), GPS1 can activate the c-Jun N-terminal kinase (JNK)/Jun pathway to affect breast cancer growth and migration (42), Saikosaponin D induced apoptosis via the activation of TGFα-JNK-p53 (43), Thymoquinone inhibits the metastasis through activation of JNK-p38 (44), JNK-ELK1 The pathway can also have an effect on the tumor (45). These are the pathways already known downstream of JNK, but there must be downstream pathways that have not been studied.…”
Section: Discussionmentioning
confidence: 99%